You don't have to graph a line to understand it. Linear equations represent lines algebraically. These equations possess many different forms, which not only act as graphing outlines but also include important and specific values. One of the most common forms is slopeintercept, where y = mx + b. In this form, "y" and "x" are variables, "m" represents the line's slope and "b" is the yintercept, the point where the line intersects the yaxis. You can find the yintercept from the slopeintercept form, or through other linear equation forms like the general and pointslope forms, through simple mathematical operations and substitutions.
Standard Form

Obtain a linear equation in standard or general form, which is a x + b y = c, where "a," "b" and "c" are coefficients. Note that the bcoefficient in this type of equation is different than the b in the slopeintercept form. For this example, allow the equation to be 3x + 5y = 15.

Convert the equation to slopeintercept form by subtracting the expression with the xvariable from each side of the equation, then divide the all expressions by the yvariable's coefficient. In this example, 3x + 5y  3x = 15  3x becomes 5y = 3x 15, and dividing all the terms by 5 results in y = 3/5x  3.

Set the xvariable to zero and then solve the equation to find the yintercept. Concluding this example, y = 3/5 * 0  3 becomes y = 3. The yintercept is 3.
PointSlope Form

Obtain a linear equation in pointslope form, which is (y  y1) = m (x  x1), where "y1" and "x1" are the Cartesian coordinates (x1, y1). For this example, allow the equation to be (y  2) = 3 (x  4).

Convert the equation to slopeintercept form by multiplying the slope to the expression in the parentheses and moving the y1 value to the right side of the equation. In this example, (y  2) = 3 * (x  4) becomes (y  2) = 3x  12, which then becomes y = 3x 10.

Set the xvariable to zero and then solve the equation for the yintercept. Concluding this example, y = 3 * 0  10 becomes y = 10. The yintercept is 10.
Tips & Warnings
 If the linear equation is given in the form y = m * x + b, just set x to zero and solve.